Scaphisoma pandemum sp. nov. (Coleoptera: Staphylinidae: Scaphidiinae) from the Atlantic Forest of Southeast Brazil - Groll, Elisa Von; Lopes-Andrade, Cristiano (Zootaxa, 2021)
Scaphidiinae (Coleoptera, Staphylinidae) comprises more than 1800 described species in 46 genera. With 766 described species and subspecies, Scaphisoma Leach is the most diverse genus of this subfamily and is distributed almost worldwide. A total of 38 species are recorded from the Neotropical region and only six are known from Brazil. In this paper, Scaphisoma pandemum von Groll & Lopes-Andrade, sp. nov. is described on the basis of 44 specimens collected from polyporoid fungi in two Atlantic Forest remnants in Viçosa, Minas Gerais, Southeast Brazil. We provide images of adult male and female and their dissected parts, information and photographs of host fungi and comparative notes.